(untitled) (Sound Stage Screen, 2024)
Review-essay of the opera Il diluvio universale. Music by Gaetano Donizetti, libretto by Domenico Gilardoni. Riccardo Frizza (Conductor), Masbedo (Project, directors, live directors and costumes), Mariano Furlani (Visual dramaturgy), 2050+ (Scenography). Teatro Donizetti, Bergamo (November–December 2023).